FAM135B sustains the reservoir of Tip60‐ATM assembly to promote DNA damage response. Issue 8 (17th August 2022) - Zhang, Kai; Wu, Qingnan; Liu, Wenzhong; Wang, Yan; Zhao, Lianmei; Chen, Jie; Liu, Haoyu; Liu, Siqi; Li, Jinting; Zhang, Weimin; Zhan, Qimin
Abstract: Background: Recently, the mechanism by which cells adapt to intrinsic and extrinsic stresses has received considerable attention. Tat‐interactive protein 60‐kDa/ataxia–telangiectasia‐mutated (TIP60/ATM) axis‐mediated DNA damage response (DDR) is vital for maintaining genomic integrity. Methods: Protein levels were detected by western blot, protein colocalisation was examined by immunofluorescence (IF) and protein interactions were measured by co‐immunoprecipitation, proximity ligation assay and GST pull‐down assays. Flow cytometry, comet assay and IF assays were used to explore the biological functions of sequence similarity 135 family member B (FAM135B) in DDR. Xenograft tumour, FAM135B transgenic mouse models and immunohistochemistry were utilised to confirm in vitro observations. Results: We identified a novel DDR regulator FAM135B which could protect cancer cells from genotoxic stress in vitro and in vivo. The overexpression of FAM135B promoted the removal of γH2AX and 53BP1 foci, whereas the elimination of FAM135B attenuated these effects. Consistently, our findings revealed that FAM135B could promote homologous recombination and non‐homologous end‐joining repairs. Further study demonstrated that FAM135B physically bound to the chromodomain of TIP60 and improved its histone acetyltransferase activity. Moreover, FAM135B enhanced the interactions between TIP60 and ATM under resting conditions. Intriguingly, the protein levels of FAM135B dramatically decreased following DNA damage stress but gradually increased during the DNA repair period. Thus, we proposed a potential DDR mechanism where FAM135B sustains a reservoir of pre‐existing TIP60‐ATM assemblies under resting conditions. Once cancer cells suffer DNA damage, FAM135B is released from TIP60, and the functioning pre‐assembled TIP60‐ATM complex participates in DDR. Conclusions: : We characterised FAM135B as a novel DDR regulator and further elucidated the role of the TIP60‐ATM axis in response to DNA damage, which suggests that targeting FAM135B in combination with radiation therapy or chemotherapy could be a potentially effective approach for cancer treatment. Abstract : High levels of FAM135B are more resistant to genotoxic stress in vitro and in vivo. FAM135B enhanced the interactions between TIP60 and ATM in resting conditions. FAM135B will be released from the pre‐assemble TIP60‐ATM module for a rapid DNA damage response.